David Vs. Goliath: Playing Against Maturity Matched or Un-Matched Opposition Results in Distinct Physical Performance and Spatial Exploration Behavior for Pre-Peak Height Velocity Basketball Athletes - Jorge Arede; Sean Cumming; Nuno Leite, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
This paper seeks to examine the impact of maturity matching upon physical performance and spatial exploration behaviour for pre-PHV basketball players. For this purpose, thirty-two under-14 to 16 basketball players are assigned to different teams according to maturity status (Pre-, Mid-, and Post-Peak Height Velocity [PHV]), and instructed to participate in basketball matches against matched (same maturity status), and un-matched (different maturity status) opposition. Maturity status is estimated considering the percentage of predicted adult height. Workload data has been collected via WIMU PRO Local Positioning System. Heart rate is recorded with individual HR monitors. Only data from pre-PHV players has been considered for further analysis. The Pre-PHV players cover greater distances when competing against post-PHV players than against matched opposition (p < 0.05, large) and Mid-PHV (p < 0.01, very large) teams. It bears to note that they perform more accelerations (p < 0.05, large) and decelerations (p < 0.05, very large) when competing against matched opposition than against the Mid-PHV teams. Furthermore, the Pre-PHV players present higher mean values for high-intensity accelerations (> 2 m∙s-2; p < 0.01, very large), average speed (p < 0.05, very large), body impacts (> 5g; p < 0.05, large), and Player Load (p < 0.01, very large) when competing against post-PHV than against Mid-PHV players. It is also found that the pre-PHV explore more space (large effect) when competing in maturity matched games than when competing against un-matched opposition teams. Pre-PHV athletes seem to benefit from playing in maturity-matched situations, to reduce the physicality of the game and to have an optimized perception of spatial-temporal information.